Primary duodenal adenocarcinoma: case report of an infrequent tumor - Óscar Moreno-Loaíza; Diana Neira-Rojas (Medwave, 2013)
Introduction. Primary duodenal adenocarcinoma is an infrequent tumor both in our environment and in the world. There is no conclusive evidence on its epidemiology, diagnostic criteria, treatment or prognosis. Clinical case. We report a 77 year-old female patient, of mixed racial origin, native of Cusco (Peru) who consulted for abdominal pain, weight loss, nausea, postprandial vomiting and bloating of three months course. At the time of examination she had second to third degree protein malnutrition with a BMI of 16.88 kg/m2, signs of moderate to severe chronic anemia and an 8 cm abdominal tumor in the epigastrium and right hypochondrium. The multislice spiral abdominal CT and ultrasonography revealed the presence of a solid tumor in the second portion of the duodenum. The patient was submitted to a gastroenterostomy without tumor resection. Biopsy confirmed tubular adenocarcinoma. Furthermore, no other primary tumors were found in the stomach, pancreas, biliary tree and colon. The patient was stabilized and was treated with 5-fluorouracil, irinotecan and leucovorin. Literature review. The article includes a brief review on the diagnosis, treatment and prognosis of this condition. Discussion. Management is not straightforward. There is little literature on the subject leaving decisions up to the attending physician’s criteria. We believe that all cases of rare diseases should be studied in depth, give rise to a thorough review of literature and, above all, be brought to the attention of the medical community.